Limb amputation in squamous cell carcinoma patient with history of leprosy - Rasikha Tsamara F; Ruth Brigitta S; Andre Setiawan; Sony Sugiharto (Institute of Computer Science (IOCS), 2023)
Leprosy is a chronic granulomatous disease affecting the skin and peripheral nerves caused by Mycobacterium leprae that results in neuropathy, deformity, and auto-amputation of digits. If auto-amputation does not occur, wound will lead to chronic skin injury which become one of risk factors for squamous cell carcinoma (SCC). Early diagnosis and prompt treatment was essential to treat chronic limb ulcer to prevent further development of SCC. To report a patient with history of leprosy with chronic ulcer in right foot that first started as a marble-sized boil a year ago. The patient underwent below knee amputation for treatment. Methods is Clinical case documentation and the patient medical record was collected and narrated chronologically in a case report. Literature review was conducted non-systematically by article database and manual searching through search engine. A 46-years old male with history of leprosy was admitted with chronic ulcer in right foot, difficulty walking and enlarged lymph nodes in both of inguinal region. The patient underwent below-knee amputation and lymph node excisional biopsy. Histopathology finding was squamous cell carcinoma without metastasis to the lymph nodes. The patient showed good outcomes post-operatively and currently undergoing rehabilitation for artificial limbs. Main treatment for SCC is wide excision, but when abnormalities are found in limbs and interferes with function, wide excision can be performed as below-knee amputation for complete treatment. This procedure can also treat chronic limb ulcer in patient with history of leprosy to prevent further development of SCC